Dynamic Fracture Toughness of TaC/CNTs/SiC CMCs Prepared by Spark Plasma Sintering - Qiaoyun Xie; Sylvanus N. Wosu (Advances in Materials Science and Engineering)
This study focuses on the fracture toughness of TaC and carbon nanotubes (CNTs) reinforced SiC ceramic matrix composites (CMCs), prepared by spark plasma sintering (SPS) technique. A high densification of 98.4% was achieved under the sintering parameter of 133°C/min, 1800°C, and 90 MPa pressure. Vickers indentation was employed to measure the indentation toughness on the polished surface of ceramic samples, SEM was applied to directly observe the crack propagation after indentation, and split Hopkinson pressure bar (SHPB) was developed to determine the dynamic fracture toughness within the ceramic samples subjected to an impact in a three-point bending configuration.